Death due to Rupture of Tubal Pregnancy - Pramod Kumar , GN; Prashanth, B M; Roopa Urs, A N; Shetty, S S; Ananthan, M A S (Journal of Indian Academy of Forensic Medicine, 2022)
Ectopic pregnancy (EP) is defined as a pregnancy in which the implantation of the embryo occurs outside the uterine cavity, most frequently in one of the two fallopian tubes or, more rarely, in the abdominal cavity. The result of an undiagnosed ectopic pregnancy is rupture of the fallopian tube with intra-abdominal bleeding, leading to hemorrhagic shock and death. Here, we present a case of 26-year old recently married female who was brought for postmortem examination with history of sudden death following pain abdomen. Postmortem examination revealed findings suggestive of ectopic pregnancy. Histopathology revealed multiple vascularized branching villi lined trophoblasts and syncytiotrophoblasts along the lumen. The significance of ectopic pregnancy lies in the fact that it often goes undiagnosed with massive intraperitoneal bleeding. This case emphasizes the need for mandatory pregnancy screening in female patients of reproductive age groups who present with abdominal pain.